2010
DOI: 10.1002/cssc.200900243
|View full text |Cite
|
Sign up to set email alerts
|

Renewable H2 from Glycerol Steam Reforming: Effect of La2O3 and CeO2 Addition to Pt/Al2O3 catalysts.

Abstract: Glycerol is the main byproduct of biodiesel production and its increased production volume derives from the increasing demand for biofuels. The conversion of glycerol to hydrogen-rich mixtures presents an attractive route towards sustainable biodiesel production. Here we explored the use of Pt/Al(2)O(3)-based catalysts for the catalytic steam reforming of glycerol, evidencing the influence of La(2)O(3) and CeO(2) doping on the catalyst activity and selectivity. The addition of the latter metal oxides to a Pt/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 75 publications
3
35
0
2
Order By: Relevance
“…Similar behavior, in terms of performance enhancement, has been observed for Pt-based catalysts promoted with basic oxides like La2O3 [92] and MgO [88]. However, the La2O3 promoted catalyst only deactivated after 50 h time-on-stream, as can be seen in Fig. 14.…”
Section: Effect Of the Addition Of A Promoter On The Catalytic Perforsupporting
confidence: 58%
See 3 more Smart Citations
“…Similar behavior, in terms of performance enhancement, has been observed for Pt-based catalysts promoted with basic oxides like La2O3 [92] and MgO [88]. However, the La2O3 promoted catalyst only deactivated after 50 h time-on-stream, as can be seen in Fig. 14.…”
Section: Effect Of the Addition Of A Promoter On The Catalytic Perforsupporting
confidence: 58%
“…Montini et al [92] verified that the Pt/CeO2/Al2O3 catalyst, despite presenting improved performance, still deactivated after 20 h time-on stream (Fig. 14) [92].…”
Section: Effect Of the Addition Of A Promoter On The Catalytic Performentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of ceria to platinum catalysts, on an alumina basis, lowers its acidic content, upgrading thereby the catalyst stability and H 2 selectivity, and lessening the formation of impurities and coke deposition [139,142]. Also, it was shown that the energy requirement for CO adsorption on Pt-based catalysts was reduced by the application of metal alloys [143].…”
Section: Catalystsmentioning
confidence: 99%